Determinants of Farm Households’ Willingness to Accept (WTA) Compensation for Conservation Technologies: Ethiopia, Amhara Region, Northern Showa - Chen T; Noufal M; Charles Melville; J Chen; T Nguyen (Information Management and Business Review, 2022)
The purpose of this study was to investigate and evaluate the WTP limits of irrigation water in the Sheva region of the Northern Amhara region of Ethiopia to understand whether irrigation water is feasible. Data were collected from primary research sources. An upright bivariate model was used to determine households’ willingness to address irrigation water problems in the study area. Using data from a sample of 800 farmers, the results show that WTP is positive for irrigation water in the North Sheva region. The results show that the average household can obtain irrigation water for about 3,001.47 0.25 hectares of land in Ethiopia, which is a one-time irrigation land value of US100.05 at the current exchange rate. In addition, the study found that household size, agricultural experience, household costs, irrigated land, livestock capital education level, and measured tropical livestock live-stock units had a positive effect on willingness to pay for irrigation water. Capital is adversely affected by family age, but market access for farmers is not guaranteed. Based on the pursuit, convincing reliability constraints, increasing market access through information and irrigation schemes, and increasing farmers’ awareness of irrigation water and its use, is the efficient use of irrigation and irrigation water. Valid maintenance conditions are recommended. Stick to discipline.